2021
DOI: 10.1097/md.0000000000025960
|View full text |Cite
|
Sign up to set email alerts
|

Macular hole with inner limiting membrane peeling off spontaneously in Terson syndrome

Abstract: Introduction: Terson's syndrome with inner limiting membrane (ILM) peeled off spontaneously is rarely seen, and the mechanism of it is not clear. Here we report a case of Terson Syndrome with a rare finding: the ILM peeled off spontaneously associated with macular hole (MH). Patient concerns: A 36-year-old female patient was admitted to our hospital with decreased visual acuity in the right eye lasting for 1 month. She just had surgery for subarachnoid hemorrhage that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…8,9 To better understand the characteristics of an MH secondary to Terson syndrome, we conducted a literature search. We found that an MH secondary to Terson syndrome was observed in only nine eyes in seven articles 4,6,[10][11][12][13][14] (Table 1). Although MH occasionally occurs as a complication of Terson syndrome, the exact cause is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 To better understand the characteristics of an MH secondary to Terson syndrome, we conducted a literature search. We found that an MH secondary to Terson syndrome was observed in only nine eyes in seven articles 4,6,[10][11][12][13][14] (Table 1). Although MH occasionally occurs as a complication of Terson syndrome, the exact cause is unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 However, Terson syndrome is associated with multiple complications, such as macular epiretinal membrane, retinal detachment, and retinal folds. 4 A delayed macular hole (MH) secondary to Terson syndrome has not been previously reported. We report a case of Terson syndrome accompanied by vitreous haemorrhage in both eyes, as well as sub-internal limiting membrane (ILM) and intraretinal haemorrhages within the macular region, which were detected during pars plana vitrectomy.…”
Section: Introductionmentioning
confidence: 99%